Pengaruh Suplementasi Dl-Methionine terhadap Berat Hidup, Berat Karkas dan Konversi Pakan Ayam Broiler - Martha Ludigadris Amleni; Charles V. Lisnahan; Gerson F. Bira (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
The aim of this study was to know the effect of dl-methionine supplementation on the body weight, carcass weight, and feed conversion of broilers. This study was conducted at the Laboratory of Animal Husbandry Study Program, Agricultural Faculty, University of Timor, Kefamenanu from December 2019 to January 2020. The study used 80 fourteen-day broilers, products by PT. Wonokoyo Surabaya, Was designed with a Completely Randomized Design, consisting of 4 treatments and 4 replications. The dietary treatments were T0 (control feed), T1 (supplementation of 0.30% dl-methionine), T2 (supplementation of 0.50% dl-methionine), and T3 (supplementation of 0.70% dl-methionine). The variables measured were body weight, carcass weight, and feed conversion. Data obtained was analyzed by analysis of variance and Duncan’s test. The result showed that the bodyweight of T0, T1, T2, and T3 were 1875.00±56.79, 2077.25±46.51, 2079.00±57.11, and 2200.50±27.74 g/bird, respectively. The carcass weight, breast weight, thigh weight, and feed conversion were 1287.40±46.14, 1457.82±27.36, 1484.42±45.13, and 1567.32±8.27 g/bird; 512.63±8.60, 584.44±14.27, 598.16±13.93, and 658.69±15.75 g/bird; 511.19±16.57, 587.86±10.48, 604.55±26.86 and 636.35±21.65 g/bird; and 2.03±0.10, 1.70±0.07, 1.66±0.05 and 1.55±0.02, respectively. Statistical analysis showed that levels of dl-methionine significantly affected body weight, carcass weight, and feed conversion (P<0.05). it can be concluded that dl-methionine supplementation of 0.70% in feed increases live weight, carcass, and feed conversion of broiler chickens.